Ambientes de aprendizajes y su impacto en el desarrollo cognitivo de los niños de subnivel II de la Unidad Educativa Emigdio Esparza Moreno - Torres Llamuca, Gilda Jamilet (2023)
Learning environments are essential for the cognitive development of children, as they influence how they perceive, process, and retain information. Early education plays a crucial role in children's personal development, promoting self-esteem and recognizing their efforts. Learning environments are divided into four categories: virtual, physical, formal, and informal, each with its own focus and benefits. Jean Piaget and his theory of cognitive development emphasize the importance of adaptation and accommodation in knowledge construction. Cognitive processes involve both basic and higher-order cognition, allowing children to acquire knowledge and solve problems as they develop. Self-regulation and assimilation are key processes in knowledge construction. The stages of cognitive development encompass the gradual acquisition of new skills and knowledge as children grow. It is important to tailor teaching to students' developmental stages to ensure effective understanding. In conclusion, it is essential for teachers to receive ongoing training in the implementation of effective learning environments. Periodic assessment of these environments, collaboration between parents and teachers, and adaptation to students' needs are also recommended. This will contribute to the cognitive development and effective learning of children. The results of a survey of teachers reflect the widespread recognition of the importance of learning environments; however, their effective implementation presents challenges. Although all teachers apply dimensions to organize these environments, the available materials are perceived as insufficient. Furthermore, the lack of training in this area underscores the need for professional development. On the other hand, parents' perceptions of these environments vary, emphasizing the importance of more effective communication and collaboration with the educational institution. Ultimately, the focus on children's cognitive development is crucial, and the improvement of teacher training, regular evaluation of learning environments, and adaptation to students' needs will contribute to effective learning and the cognitive development of children.